Chef's social platform - Hsiao, Chia Yu (Nanyang Technological University, 2021)
Social interaction is the key factor to the quality of life, lacking it may affect one’s mental well-being. Motivated by the increasing demand in social media and home cook trends, the project aims to promote social interaction by creating social media on a culinary domain for the community to share and learn cooking skills together. A native Android application Elite Chef is developed with an illustration of thinking processes in stages of the software development life cycle.